The Religious Values Existence on Pekalongan Batik Cultural Heritage - Haryati, Tri Astutik; Zuhri, Amat; Kosim, Mohammad; Dahri, Harapandi (Universitas Islam Negeri Madura, 2024)
This study explores the cultural heritage of Pekalongan batik, which holds the identity of the City of Batik and the City of Santri. The analysis focuses on the economic, cultural, and Islamic roles and how they determine the existence of batik businesses that have persisted until now. This study uses a cultural approach with case study analysis and finds that batik businesses transmit a cultural heritage that continues from generation to generation until batik becomes a cultural identity and the lifeblood of Pekalongan's economy. Cultural transmission occurs socially, through learning processes, interaction among peers, socialization in society, skill mastery cadreship, and batik business management. As a source of grassroots economy, batik is integrated into society's daily activities, crystallizing in mindset as tradition and implicating in the development and preservation of batik that always follows the dynamics of the times. The cultural inheritance of batik cannot be separated from the role of religion, which serves as a source of moral vitality and a means to preserve the existence and sustainability of batik business.